Pemberdayaan Pendidikan Vokasional: Pelatihan Mesin Laser cutting untuk Keterampilan Desain dan Fabrikasi di SMKN 9 Batam - Leksonowati, Nur Fitria Pujo; Batubara, Ninda Hardina; Purba, Adi Syahputra; Cahyagi, Danang; Butar, Hendra Butar; Wijayanti, Ita; Manurung, Meilani Mandalena; Dzulfikar, Mohamad Alif; Stefani, Windy; Ulfah, Nurul; Aryswan, Adhe; Pamungkas, Nurman; Khollilurrahman, Kholillurrahman (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2024)
This community service initiative aims to enhance the skills of vocational school students in utilizing Laser cutting machines, serving as a platform for students in the Design and Visual Communication department of SMKN 9 Batam to fabricate products based on their own designs in preparation for the professional world. The participants involved in this initiative consist of 78 students from the aforementioned department. The community service program is structured through various stages, encompassing initiation, preparation, execution, activity review, and the compilation of a final report. Enthusiastically engaged, the participants, primarily from the Design and Visual Communication department, had previously focused their learning solely on the design phase. However, through this community service project, they actively participated in the fabrication process of designs they had created. Utilizing CAD applications, the designs were transformed into tangible products using acrylic as the raw material, ensuring that the resulting products align with the envisioned design. This initiative provides a valuable avenue for students to bridge the gap between design and fabrication, fostering practical skills crucial for their future endeavors in the workforce.